Pengaruh Tingkat Suku Bunga SBI dan Kurs Nilai Tukar Rupiah Terhadap Dolar AS Terhadap Harga Saham Perusahaan Farmasi Di Bursa Efek Jakarta - Sri RUSIYATI (Universitas Bina Sarana Informatika, 2017)
This study was aimed to determine the effects of SBI interest rate and Rupiah to US Dollar exchange rate on the stock prices of pharmaceutical companies in Jakarta Stock Exchange.The hypothesis was there were SBI interest rate (X1) and Rupiah to US Dollar exchange rate (X2) were suspected to have significant effect on the stock prices (Y) of Domestic and Foreign Investments pharmaceutical companies in Jakarta Stock Exchange. This study used Multiple Linear Regression Analysis and Multiple Correlation. The hypothesis was examined by F statistic test (Anova) and t statistic test.The result of data analysis showed that SBI interest rate (X1) and Rupiah to US Dollar exchange rate (X2) had simultaneous significant effect on the stock prices (Y) of Domestic and Foreign Investments pharmaceutical companies. The stock prices of Domestic and Foreign Investments pharmaceutical companies in Jakarta Stock Exchange were affected by the independent variables, which were SBI interest rate and Rupiah to US Dollar exchange rate, by 56,9% in domestic investment pharmaceutical companies and 65,60% in foreign investment pharmaceutical companies. The rest was explained by other variables such as company performance, inflation, political factor, etc..Multiple regression equation didn’t guarantee wasn’t feasible for predicting future stock prices because not all regression coefficients significantly affected the stock prices of Domestic and Foreign Investments pharmaceutical companies in Jakarta Stock Exchange.